2020
DOI: 10.1007/s12021-020-09491-7
|View full text |Cite
|
Sign up to set email alerts
|

An MRI-Based, Data-Driven Model of Cortical Laminar Connectivity

Abstract: Over the past two centuries, great scientific efforts have been spent on deciphering the structure and function of the cerebral cortex using a wide variety of methods. Since the advent of MRI neuroimaging, significant progress has been made in imaging of global white matter connectivity (connectomics), followed by promising new studies regarding imaging of grey matter laminar compartments. Despite progress in both fields, there still lacks mesoscale information regarding cortical laminar connectivity that coul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…After selecting the best fitting routine for standard connectivity analysis, white and grey matter datasets were integrated through a novel model of cortical laminar connectivity (Shamir and Assaf 2021). We used the Circular-Connectome toolbox (available at: github.com/ittais/Circular-Connectome) to visualize both the model input datasets as well as the resulting model output in circular graph formats.…”
Section: Discussionmentioning
confidence: 99%
“…After selecting the best fitting routine for standard connectivity analysis, white and grey matter datasets were integrated through a novel model of cortical laminar connectivity (Shamir and Assaf 2021). We used the Circular-Connectome toolbox (available at: github.com/ittais/Circular-Connectome) to visualize both the model input datasets as well as the resulting model output in circular graph formats.…”
Section: Discussionmentioning
confidence: 99%
“…This study presents an innovative exploration of a network model of the healthy human connectome on the laminar level. This model embodies a simplified set of laminar-level rules of connections, based on a systematic review of histological tract tracing studies (Shamir and Assaf 2021a). While this model has been corroborated ex-vivo in the macaque brain (Felleman and Van Essen 1991; Shamir and Assaf 2021b), corroborating the results in-vivo in the human brain is a more nuanced task.…”
Section: Statements and Declarations Fundingmentioning
confidence: 99%
“…The integration of macrostructural data regarding white matter connectomics and microstructural data regarding grey matter laminar composition poses a promising development in the field of connectomics (Johansen-Berg 2013). A recently published study offers a simplified granularity-based model of cortical laminar connectivity based on published tract tracing and histological findings, with the purpose of Modelling the laminar connectome of the human brain 3 integrating white and grey matter datasets derived from multimodal MRI imaging (Shamir and Assaf, 2021a). The model is then further explored in the macaque brain and corroborated in its visual cortex by comparison to published studies (Shamir and Assaf 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Even with the advent of high-resolution functional neuroimaging, multilayer connectomics have mostly focused on anatomical networks derived from structural MRI and DTI [57, 58] due to their direct relationship to cortical architecture. For example, DTI and histological samples identified that cortical areas with similar laminar structure were more likely to be connected [59].…”
Section: Introductionmentioning
confidence: 99%